A phytochemical investigation of Peperomia pellucida (L.) Hbk. (Fam. Piperaceae) - Manalo, Josefina (Buenaventura) 1933-
Potassium nitrate (KNO3), an inorganic salt, was isolated from the ethanol fraction of Peperomia pellucida (L.) HBK. as a white crystalline powder. Its identity was established by chemical tests and by analysis of its IR spectrum. From the neutral ether fraction of the whole plant, 4, 7-dimethoxy-5-(2-propenyl)-1, 3-benzodioxole or apiol, with a parsley odor; a 2, 4, 5-trimethoxy styrene, mp 176-178(degrees), and three phytosterols namely: campesterol, stigmasterol and beta-sitosterol, were isolated and characterized by spectrophotometric methods.